2020
DOI: 10.1111/joa.13300
|View full text |Cite
|
Sign up to set email alerts
|

A mechanistic approach for the calculation of intervertebral mobility in mammals based on vertebrae osteometry

Abstract: In this paper, we develop and validate an osteometry-based mechanistic approach to calculation of available range of motion (aROM) in presacral intervertebral joints in sagittal bending (SB), lateral bending (LB), and axial rotation (AR). Our basic assumption was the existence of a mechanistic interrelation between the geometry of zygapophysial articular facets and aROM. Trigonometric formulae are developed for aROM calculation, of which the general principle is that the angle of rotation is given by the ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(48 citation statements)
references
References 46 publications
0
48
0
Order By: Relevance
“…To calculate intervertebral mobility, we used a recently developed and validated osteometry‐based method (Belyaev et al, 2021). It is based on the assumption of the functional interrelation between aROM and the geometry of vertebrae and, in particular, of zygapophyseal articular facets (Kuznetsov & Tereschenko, 2010).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…To calculate intervertebral mobility, we used a recently developed and validated osteometry‐based method (Belyaev et al, 2021). It is based on the assumption of the functional interrelation between aROM and the geometry of vertebrae and, in particular, of zygapophyseal articular facets (Kuznetsov & Tereschenko, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…In the course of evaluation of the optimal formulae for calculating aROM values, it was found that separate formulae for different zygapophyseal facet types (radial [Rf], tangential [Tf], radial with a lock [RfL]) give significantly greater accuracy in aROM calculation than the formulae for the presacral vertebral column as a whole, and greater accuracy than the separate formulae for different vertebral column regions (cervical, thoracic, and lumbar) (Belyaev et al, 2021). In artiodactyls, the Rf type (left and right facets together form a V‐like pattern in the transverse plane) is present in the cervical region and the neck–thorax transition (joints C2–T1), plus the T1–T2 joint in Tayassu , Pecari , Giraffa , and, as individual variation, in Choeropsis .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A center of rotation was found by fitting (i.e., manually adjusting size and position) a semitransparent sphere matching the curvature of the zygapophyseal facets of C7 with the sphere's surface from the lateral and dorsal perspectives (see Kuznetsov and Tereschenko, 2010; Belayaev et al. 2020 for a similar approach of using zygapophyseal curvature; SI 8). Next, a Maya “joint” is placed into the center of the fitted sphere (cf.…”
Section: Methodsmentioning
confidence: 99%